(3GdefJgi aj GdceGds - (3eMeO Hf Sgd Hf GdeQRHGf GdHZOGOj GdcQNj, CHh efUhQs
(3ChdgG (B:s
(3cJGH GdJTHjgGJ hGdWdH PcQ CHhGH GdcJGH HYO GdQSGdI s
(3BNQgG (B:s
(3EPG eG CgGfJ HGNdkG TMjMkG QZGFH GehGd aCfJ JgjgfG s
(3HQhGjGJ CHj eMeO YHjOGddg Hf eMeO Hf Lejd GdcQNi ChQGbgG eVWQHg GdJQJjHs
(3cGf GdeDda MjkG SfI (B300 (3g`s
(3heYg cJGH GdJgGfi hGdJYGRi hcJGH GdBed hGdeCehd hcJGH GdJTHjgGJ hGdWdH hcJGH GdENhGfjGJs
(3hcJGH GdSdWGfjGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B58s
Keywords: (3GdCOHs